2014
DOI: 10.5935/abc.20140054
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 Hypomethylation is Associated with the Risk of Coronary Heart Disease in Chinese Population

Abstract: BackgroundGlobal methylation level in blood leukocyte DNA has been associated with the risk of coronary heart disease (CHD), with inconsistent results in various populations. Similar data are lacking in Chinese population where different genetic, lifestyle and environmental factors may affect DNA methylation and its risk relationship with CHD.ObjectivesTo examine whether global methylation is associated with the risk of CHD in Chinese population.MethodsA total of 334 cases with CHD and 788 healthy controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…In total, 51 articles met our eligibility criteria (Supplementary Table 1) and were included in the analysis. Of the 51 selected studies, 17 included participants from Europe [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] 14 from China [23][24][25][26][27][28][29][30][31][32][33][34][35][36], six from USA [37][38][39][40][41][42], three from India [43][44][45], two from Canada [46,47], and one each from Japan [48], Malaysia [49], Iran [50], Russia [51], Brazil [52] and Mexico [53]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 51 articles met our eligibility criteria (Supplementary Table 1) and were included in the analysis. Of the 51 selected studies, 17 included participants from Europe [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] 14 from China [23][24][25][26][27][28][29][30][31][32][33][34][35][36], six from USA [37][38][39][40][41][42], three from India [43][44][45], two from Canada [46,47], and one each from Japan [48], Malaysia [49], Iran [50], Russia [51], Brazil [52] and Mexico [53]…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies analyzed global DNA methylation [6,7,23,34,36,42,52], 31 followed a candidate-gene approach [8][9][10][11][12][13][14]20,22,[24][25][26][27][28][29][30][31][32][33]35,[38][39][40][41]45,46,49,50,[54][55][56], seven were epigenome-wide association studies (EWAS) [16,18,19,21,44,48,53], two used both global DNA methylation and candidate-gene approaches [37,43], three used EWAS and global DNA methylation approaches [15,17,51], and on...…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Epigenetic marks such as DNA methylation of cytosine residues in CpG dinucleotides have been shown to be helpful in the advance diagnosis of CHD (Wei et al, 2014). SNPs rs3918250 and rs2075847 are promoter CpG polymorphisms and might therefore affect gene expression, although evidence is needed to support this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Participants older than 65 years had a 1.46‐fold increased risk of higher SHMT1 promoter methylation. Consistent with our study, previous studies also indicated a positive association between increased DNA promoter methylation, such as that for ADD1 and LINE‐1 , and older age. Changes in DNA methylation may be induced by aging and environmental exposures …”
Section: Discussionmentioning
confidence: 99%